(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2026)
Abstract - The rapid expansion of hybrid work models has transformed contemporary work environments, particularly for Generation Z employees. This study investigates the relationship between hybrid work systems, employee productivity, work–life balance, and technostress, with a focus on the mediating role of technology-related stress. A quantitative cross-sectional survey was conducted among 215 participants, primarily consisting of students and freelancers engaged in flexible work arrangements. Data were analyzed using descriptive and inferential statistical methods. The findings reveal a highly polarized pattern of responses, indicating that hybrid work produces both positive and negative outcomes rather than uniform effects. While a majority of respondents expressed a preference for hybrid work, the results demonstrate moderate mean scores for productivity (M = 5.5), work–life balance (M = 6.2), and technostress (M = 5.8), accompanied by relatively high standard deviations. This suggests substantial variability in individual experiences. Hybrid work was found to enhance productivity and work–life balance under favorable conditions, such as reduced commuting time and increased autonomy. However, challenges related to boundary management and technostress were also identified, limiting its effectiveness for some individuals. The study confirms the mediating role of technostress and highlights the importance of work– life balance as a predictor of productivity. The findings are interpreted through the Job Demands– Resources (JD-R) model, demonstrating that hybrid work simultaneously functions as both a resource and a demand. The study contributes to the growing literature on flexible work by emphasizing the context-dependent nature of hybrid work outcomes and the need for adaptive organizational strategies.